2019
DOI: 10.3390/ani9080536
|View full text |Cite
|
Sign up to set email alerts
|

Use of Licorice (Glycyrrhiza glabra) Herb as a Feed Additive in Poultry: Current Knowledge and Prospects

Abstract: Simple SummaryThe present review updates the current knowledge about the beneficial effect of licorice supplementation in poultry diets, particularly its positive effect on the treatment of high-prevalence diseases of the immune system, liver, and lungs.AbstractSupplementation of livestock and poultry diets with herbal plants containing bioactive components have shown promising reports as natural feed supplements. These additives are able to promote growth performance and improve feed efficiency, nutrient dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 40 publications
(72 reference statements)
1
73
0
2
Order By: Relevance
“…Globally, the poultry industry is one of the major agricultural subsectors [1]. According to an Food and Agriculture Organization of the United Nations (FAO) report, there is a total of about 1210 million, including 87.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the poultry industry is one of the major agricultural subsectors [1]. According to an Food and Agriculture Organization of the United Nations (FAO) report, there is a total of about 1210 million, including 87.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of antibiotics as a growth stimulant in animal feed was banned in Europe. Revolution in animal feed production has resulted in the development of feed additives in the forms of phytogenics [2,3]. Herbs and their metabolites (known as bioactive substances) play a good role as feed additives.…”
Section: Introductionmentioning
confidence: 99%
“…50 mg/kg LE reduced TC and HDL-C in serum (Table 2), similar results are found that supplementation of LE through drinking water reduces the serum glucose, low density lipoprotein cholesterol (L-DLC) and total cholesterol in broilers [29]. This decreases of serum TC and HDL-C may be related to the inhibition of lipid peroxidation by licorice, the active ingredient of licorice inhibits the formation of lipid peroxides, and in the subsequent liver clearance process increases the rate of conversion of cholesterol into bile acids, thereby reducing cholesterol and increased liver bile acid content [30]. LE had no effect on the spleen index and kidney index of weaned piglets (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of serum IgG indicated enhancement of the serum immunity of weaned piglets by dietary LE. The active ingredients in licorice extract, such as glycyrrhizin avonoids and glycyrrhizic acid, increase the phagocytic function of phagocytic cells and regulate the number and function of lymphocytes [49], thus prevent some in ammatory mediators by regulating immune-related signaling pathways or enzyme activities produced to activate macrophages, indirectly inhibit platelet aggregation [30], in ammatory cytokine secretion [30,50] and neutrophil adhesion [43,51], thus regulate the in ammatory response and improve immune function of piglets.…”
Section: Discussionmentioning
confidence: 99%